Toll Road Construction: The Concept of Justice and Community Peace Against Environmental Change - Muyasaroh Muyasaroh; Herlina Herlina (International Journal of Emerging Issues in Islamic Studies, 2023)
The Ministry of Public Works and Public Housing (PUPR) always encourages the completion of toll roads in every region in Indonesia in accelerating barrier-free connectivity for the community, one of which is the Trans Sumatra toll road at the Indralaya - Muara Enim intersection along 119 km. The purpose of this study is to find the right and appropriate pattern for the community around the toll road construction so that justice and peace can be realized over the environmental changes. This study uses a qualitative approach with inductive data analysis. Data collection is done repeatedly and continuously with triangulation techniques to produce a concept. Types and strategies in research are case studies. The analysis tools used are NVivo 12 Plus. The results of the study found a concept that creates justice and peace in the community due to the construction of toll roads. Environmental changes that occur must be based on the principle of benefit and benefit. The construction of toll roads must involve the local community in order to create conducive conditions in the pre, process and post-implementation processes. Negative impacts on the environment in the development process must be minimized through dialogue and contributions from the surrounding community. The conclusion of this study is that the construction of the Indarala – Muara Enim toll road as a whole is classified as meeting the requirements of the needs of the benefit, but there is still a lack of anticipation from this implementation project because there are still community complaints that can be read from respondents' responses. Environmental changes related to toll road construction must use a structured and orderly concept. In this case, the concept of environmental change must be bound by rules and regulations to anticipate and provide solutions for the negative impacts that occur and will occur, in the form of minimal compensation for land or land and buildings affected by the project. at a reasonable price, dealing with contaminated or polluted air and noise quickly and responsively.